Relationship Between Age, Work Period, Work Load with Work-Realted Stres (Study on Education Personnel at the Directorate od Health Polytechnic, Ministry of Health, Surabaya in 2025) - Septia Dwi Cahyaningtyas; Winarko Winarko; Winarko Winarko; Avita Amalina; Demes Nurmayanti (Jurnal Kesehatan Terpadu, 2026)
Work stress can be experienced by every worker, including educational staff, and can disrupt health, thereby reducing work productivity. Work stress can be influenced by many factors, both internal, external, and worker-related factors. This study aims to analyze the relationship between age, length of service, and workload with the level of work stress among educational staff at the Directorate of Poltekkes Kemenkes Surabaya in 2025. The method used in this study is an analytical observational approach with a cross-sectional design. The sample size of 63 educational staff was randomly taken from 74 educational staff. The research results show that 100% of educational staff experience stress, with the highest being 100% experiencing work-related stress, with 4.8% in severe condition and 52.4% in moderate condition. Additionally, 92.1% are over 30 years old, 65.1% have worked for ≥ 5 years, and 65.1% have a high workload. It is concluded that work experience and workload have a significant relationship with work stress (p < 0.05), while age has no relationship with work stress (p > 0.05). It is recommended to conduct monitoring and evaluation of work stress every 6 months, and recreational activities annually.